Exchange Rate – Relative Price Nonlinear Cointegration Relationship in Malaysia - Venus, Khim-Sen Liew; Kian−Ping, Lim; Evan, Lau; Chee-Keong, Choong (AccessEcon, 2005)
The finding of exchange rate–relative price nonlinear cointegration relationship in Malaysia, among others, suggests that nonlinear Purchasing Power Parity (PPP) equilibrium may be regarded as reference point in judging the short run misalignment of the Ringgit currency and thereby deducing effective policy actions. Moreover, economists who wish to extend the simple PPP exchange rate model into the more complicated monetary exchange models may do so comfortably, at least in the text of Malaysia. Nonetheless, such attempt should be tailored in a nonlinear way to suit the nonlinear characteristic of exchange rate behaviour